(untitled) (Biological Sciences - PJSIR, 2001)
Form Central Punjab, Pakistan , a new species (Hypopus) F tumulus of the family Acaridae i s described and docu mented. It belongs to the genus Forcellinia Oudemans , 1924. Differential features are i ntegrated in to key and characters of the species are compared with those of the world known species.